Batas Pertanggungjawaban Pidana Tenaga Medis dalam Pelayanan Rehabilitasi Terpidana Narkotika - Steven S. Gugu (Jurnal Ilmiah Kesehatan, 2026)
The rehabilitation services for convicted narcotics offenders involve medical professionals who have the authority to conduct assessments, diagnoses, therapies, and patient monitoring. In its implementation, legal issues arise concerning the limits of criminal liability of medical personnel when medical risks, negligence, or harmful consequences to patients occur. This study aims to analyze the legal regulation of rehabilitation services for convicted narcotics offenders and to examine the limits of criminal liability of medical personnel from a health law perspective. This research employs a normative legal research method using a statutory approach and a conceptual approach through a literature review. The findings indicate that the regulation of narcotics rehabilitation has not explicitly established the boundaries between medical risks inherent in professional medical actions and misconduct that may give rise to criminal liability. Criminal liability of medical personnel may only be imposed when there is an element of a criminal offense, fault in the form of intent or negligence, and a causal relationship between the medical action and the resulting consequences. Therefore, clear legal norms are required to provide legal certainty and protection for medical personnel in carrying out rehabilitation services for convicted narcotics offenders.